Just Don't Know How She Does It: a Feminist's Showroom of Subversive Machinations - Robertson, Emily Harriet Bulbring (Michaelis School of Fine Art, 2024)
I have created a body of work that takes the form of a series of inventions or products aimed at giving their users the appearance of conforming to existing gender stereotypes pertaining to the roles of women, whilst actually allowing them to live a life of their own choosing. I have communicated my intentions through the media of collage, montage, installation and mixed-media assemblage. The collective body of work is displayed in the mode of a showroom, as one might encounter in a home exposition or convention. Some of the stereotypes I have found most pervasive in my lived experiences, and those of the women I know, include sentiments such as: all women should be docile and submissive; a woman's life is incomplete without a husband and child; women's primary concerns should be the domestic space and serving their families; a career or other personal goals should never be prioritised over family and home; a woman's body and sexuality is purely for male pleasure and consumption, and she should be damned if she behaves otherwise. As a point of departure in the development of this project I have focused on how these stereotypes are perpetuated within popular culture. I have taken cues from Pop art especially concerning the way in which these artists have employed images and objects from everyday consumer culture. To recall, Pop art was a movement that emerged in the 1950s and responded to the increasingly pervasive and omnipresent consumerist culture. Through mimicry of consumer product design and making use of mass media objects, artists critiqued the agendas of their capitalist society. One of the major instances of parody that occurred within the movement was in the elevation of ordinary products or celebrities to subject matter for high art, such as in Andy Warhol's Campbell Soup Cans (1962) or in Jeff Koons's New Shelton Wet/Dry Doubledecker (1981). The framing of consumer culture as high art invited a reconsideration of the value of such objects as well as the institution of high art. The title of this exhibition acknowledges its Pop art lineage, as it references Richard Hamilton's seminal collage piece Just what is it that makes today's homes so different, so appealing? (1956). The inter-textual reference to Hamilton's work is further articulated by my use of collage and the ironic, self-aware employment of references to consumer culture. Artists working within the Pop milieu, such as Hamilton, are noted for their use of irony and parody, which cuts into both consumer culture and fine art practices. Such double-edged critique also underpins this project